Analisis Kebutuhan Buku Ajar Siap Menghadapi Haid pada Pondok Pesantren Bahrul Ulum Induk Tambakberas Jombang - Muhammad Fahmi Cholqi; Siti Sulaikho (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The purpose of this study was to find out how much the students of the Bahrul Ulum Tambakberas Jombang Islamic Boarding School needed the textbook Ready to Face Menstruation. The results of this analysis can later be used as a benchmark for how much the students at the Bahrul Ulum Tambakberas Jombang Islamic Boarding School need the textbook Ready to Face Menstruation. Research conducted is part of quantitative research. By taking a sample of 35 students from 850. The highest percentage results were obtained from the questionnaire items 1 to 14, namely 79.7% (Required) on item 12. In the process of teaching and learning Fiqh Menstruation, Nifas, and Istihadoh, teachers really need innovations that make easy and enthusiastic students. So we need a reference book that is used by the teacher to make it easier for the students. Based on the results of the research on the needs of the students of Bahrul Ulum Induk Islamic Boarding School Tambakberas Jombang for the textbook Ready to Face Menstruation, it can be concluded that the students really need textbooks that contain and make it easy to learn the fiqh of Menstruation, Nifas, and Istihadoh with a percentage score of 79, 7% (Required).